(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Internal Limiting Membrane (ILM) peeling, currently, due to more successful hole closure rate and prevention of postoperative reopening, has been accepted globally but it may leads to other trivial complications like subretinal and retinal hemorrhage, vitreous hemorrhage and retinal edema etc., which may be avoided by using adjuvant instruments, like Finesse flex Loop. The aim of this study was to compare complications after ILM peel, with and without finesse loop. Patients and methods: In this comparative cross-sectional study conducted in Ophthalmology Department of Lahore General Hospital, Lahore from February 2018 to January 2019, the data of thirty (30) patients was compared after taking informed consent through self-made pro-forma. Data analysis was done on SPSS-21. Frequency / percentage table of qualitative variables like retinal hemorrhage, retinal tear, retinal detachment and surface irregularities were designed by using excel-16. Fischer’s exact test was applied to compare complications after ILM peeling with and without using Finesse loop. Confidence interval of 0.95 with α of 0.05 was taken as significant. Results: This study included thirty (30) patients (female: 13; male: 17) with mean age of 56 years and 8 months. Comparison between outcomes of ILM peeling with and without using Finesse™ Flex Loop showed that there is statistically non-significant difference in occurrence of retinal hemorrhage (p=0.245), retinal tear (p=0.224), retinal detachment (p=1.00) and surface irregularities (p=0.39). However, the prevalence of complications like surface irregularities, retinal tear, retinal hemorrhage and retinal detachment with finesse loop were less as compared to without finesse loop. Conclusion: The prevalence of complications during ILM peel with finesse loop in a macular hole surgery, were less than that in ILM peel with ILM forceps alone.